The assessment of lens opacities in clinical practice: results of a national survey - Frost, N (2001)
AIM—To investigate the examination of lens opacities in routine ophthalmic clinical practice. METHOD—A questionnaire survey was mailed to 703 consultant ophthalmologists in the UK. The surgeons were asked which lens feature(s) they assessed in their clinics when deciding whether to offer cataract surgery. RESULTS—489 replies were received. A broad range of lens opacities was assessed, with differences between surgeons for some opacities with high prevalences in the population, particularly cortical opacities. Many (74% of 467) surgeons assessed one or more lens opacities (anterior subcapsular cataract, vacuoles, water clefts, coronary flakes, focal dots, retrodots, fibre folds) which may be visually important but which have received relatively little attention by researchers. CONCLUSIONS—Some classes of lens opacity which are traditionally measured by researchers may be ignored in clinical practice and opacities which are traditionally ignored by some researchers are regarded as clinically important by a substantial number of surgeons.